2010
DOI: 10.1089/jop.2009.0120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nitric Oxide Releasing Prostaglandin Analog, NCX 125, Reduces Intraocular Pressure in Rabbit, Dog, and Primate Models of Glaucoma

Abstract: NCX 125, a compound targeting 2 different mechanisms, is endowed with potent ocular hypotensive effects. This may lead to potential new perspectives in the treatment of patients at risk of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…A nitric oxide-releasing prostaglandin analog was shown to produce a larger IOP reduction compared with latanoprost alone in ocular hypertensive rabbits, dogs, and monkeys. 42 Gene therapy in targeted sites where pharmacologic delivery of nitric oxide donors may not reach sufficient concentrations for therapeutic purposes may be a viable option as well. 43 Endothelial NOS would be a likely candidate.…”
Section: Discussionmentioning
confidence: 99%
“…A nitric oxide-releasing prostaglandin analog was shown to produce a larger IOP reduction compared with latanoprost alone in ocular hypertensive rabbits, dogs, and monkeys. 42 Gene therapy in targeted sites where pharmacologic delivery of nitric oxide donors may not reach sufficient concentrations for therapeutic purposes may be a viable option as well. 43 Endothelial NOS would be a likely candidate.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of animal studies indicate that the pharmacologically modified drugs are more efficacious than their respective prostaglandin counterparts. [116][117][118] Recently, it was announced that BOL-303259-X, a nitric oxide-donating latanoprost analogue was superior to latanoprost in reducing IOP in patients with glaucoma or OHT. 119 Prostaglandin analogues can also be modified to release hydrogen sulfide (H 2 S), a gas that has antioxidative properties.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…In human eyes, NOS reactivity was enriched in major sites of outflow resistance, including the TM and SC, as well as in collecting channels. 16 The NO-donating compounds effectively decrease conventional outflow resistance, leading to a decrease in IOP and outflow rate in different animal models, including rabbits, [21][22][23][24] pigs, 25 dogs, 22 and monkeys, 22,26 and in perfused postmortem human eyes. 27,28 Our previous study 29 further showed that eNOS/NO is a key regulator of outflow facility and IOP in mice.…”
mentioning
confidence: 99%